Model for stamina development in biathletes based on the combined application of respiratory exercises - Bolotin, A.; Bakayev, V. (SportMont, 2019)
Studies have shown that the adaptation of biathletes` bodies to different loads takes place gradually from stage to stage due to the development of stamina in the framework of the combined use of respiratory exercises. The process of adaptation and change in functional parameters characterizing physical performance and functioning of external respiration occurs mainly due to the expansion of the range of application of the means that expand the capabilities of the cardiorespiratory system of the biathlete`s body. The use of respiratory exercises with and without exercise machines in combination with aerobic exercises of moderate, medium, and maximum intensity allows expanding the reserve and functional capabilities of the biathlete`s body. This allows achieving more significant positive changes in general and specific physical fitness, physical performance, functional fitness, breathing capacity and biathlete reserves, as well as the rates of response to different loads during training sessions.